2020
DOI: 10.2147/ott.s251157
|View full text |Cite
|
Sign up to set email alerts
|

<p>KIAA1522 Promotes the Progression of Hepatocellular Carcinoma via the Activation of the Wnt/β-Catenin Signaling Pathway</p>

Abstract: KIAA1522 was previously identified to play a crucial role in cancer development and progression. However, its functions and underlying mechanisms in hepatocellular carcinoma (HCC) remain elusive. Materials and Methods: To elucidate the role of KIAA1522 in HCC, its expression was assessed using The Cancer Genome Atlas and GEPIA databases. Next, these results were validated by quantitative reverse transcription-polymerase chain reaction, Western blotting, and immunohistochemistry of HCC tissues and cell lines. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…In order to account for the effects of age and gender on unfavorable outcomes, AFP in serum, univariate, and multivariate analyses were carried out, which suggests that KIAA1522 is a possible prognostic and diagnostic marker. Recent reports [ 14 , 15 ] agree with the findings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In order to account for the effects of age and gender on unfavorable outcomes, AFP in serum, univariate, and multivariate analyses were carried out, which suggests that KIAA1522 is a possible prognostic and diagnostic marker. Recent reports [ 14 , 15 ] agree with the findings.…”
Section: Discussionsupporting
confidence: 88%
“…The mRNA expression of KIAA1522 was elevated in a number of malignancies, according to data from the Gene Expression Atlas and The European Bioinformatics Institute databases, which showed that abnormal KIAA1522 expression may have a role in the pathogenesis and growth of cancer [ 13 ]. Recent research demonstrated that elevated KIAA1522 expression accelerated the evolution of HCC by activating the Wnt/ β -catenin pathway and predicted a poor prognosis in HCC patients [ 14 , 15 ]. The function of KIAA1522 in human cancer immunology, however, has hardly ever been thoroughly examined.…”
Section: Introductionmentioning
confidence: 99%
“…The above findings also suggested that KIAA1522 might be a potential therapeutic target in CRC. Functional studies revealed that high expression of KIAA1522 promoted the proliferation, survival, migration and invasion of CRC cells [48] . Whether KIAA1522 has other functional roles in CRC cells, such as regulating the cell cycle and EMT, remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It is a newly cloned gene with unknown functions. 25 In addition, there have been a few functional studies documenting that overexpression of KIAA1522 is associated with human cancers, including esophageal squamous cell carcinoma, Ewing sarcoma, and nonsmall cell lung cancer. [26][27][28][29][30] These studies demonstrated that KIAA1522 plays a critical role in cell adhesion and apoptosis inhibition.…”
Section: Discussionmentioning
confidence: 99%